Confessions of a SHOPAHOLIC - Kinsella, Sophie (New York : A DELL BOOK, 2009)
Becky has a fabulous flat in London's trendiest neighborhood, a troupe of glamorous socialite friends, and a closet brimming with the season's must-haves. The only trouble is that she can't actually afford it - not any of it.
Keywords: Young women -- Fiction; Shopping -- Fiction; Debt -- Fiction; Young women -- London (England) -- Fiction